Performance Management in Islamic Boarding Schools: Implementing Balanced Scorecard and Key Performance Indicators - Sumiati, Iis; Aedi , Nur; Permana , Johar; Amaliah, Nurrohmatul (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2026)
Educational institutions face increasing demands for accountability, effectiveness, and strategic performance management. This study aims to examine the implementation of the Balanced Scorecard (BSC) as a performance management tool in an Islamic boarding school. A qualitative case study design was employed at Nurul Fikri Boarding School Lembang. Data were collected through semi-structured interviews with school leaders, teachers, and educational staff, supported by observations and document analysis. The data were analyzed using thematic analysis to identify key patterns related to BSC implementation. The findings reveal that BSC implementation has been initiated and is primarily understood at the leadership level, while understanding among teachers and staff remains uneven. Performance indicators are formulated through a predominantly top-down process within each work unit and implemented through routine performance evaluations; however, their application is not yet optimal due to limited data availability and constrained human resource capacity. The study also finds that the integration of Islamic values into performance indicators has not been systematically standardized. Leadership commitment, foundation support, and the availability of strategic planning documents were identified as key supporting factors for BSC implementation. In conclusion, while the Balanced Scorecard has begun to function as a performance management framework, strengthening understanding across organizational levels, improving data systems, and developing Islamic values-based performance indicators are necessary to enhance its effectiveness. These findings imply the need for capacity building, data infrastructure development, and contextual adaptation of BSC in Islamic educational institutions.